Interventions for treating cholestasis in pregnancy (Review) - Gurung, Vinita; Stokes, Michael; Middleton, Philippa; Milan, Stephen J.; Hague, William; Thornton, Jim (Wiley, 2013)
BACKGROUND: Obstetric cholestasis has been linked to adverse maternal and fetal/neonatal outcomes. As the pathophysiology is poorly understood, therapies have been empiric. The first version of this review, published in 2001, and including nine randomised controlled trials involving 227 women, concluded that there was insufficient evidence to recommend any of the interventions alone or in combination. This is the first update. OBJECTIVES: To evaluate the effectiveness and safety of therapeutic and delivery interventions in women with cholestasis of pregnancy. SEARCH METHODS: We searched the Cochrane Pregnancy and Childbirth Group's Trials Register (20 February 2013) and reference lists of identified studies. SELECTION CRITERIA: Randomised controlled trials that compared two intervention strategies for women with a clinical diagnosis of obstetric cholestasis. DATA COLLECTION AND ANALYSIS: The review authors independently assessed trials for eligibility and risk of bias. We independently extracted data and checked these for accuracy. MAIN RESULTS: We included 21 trials with a total of 1197 women. They were mostly at moderate to high risk of bias. They assessed 11 different interventions resulting in 15 different comparisons.Compared with placebo, ursodeoxycholic acid (UDCA) showed improvement in pruritus in five (228 women) out of seven trials. There were no significant differences in instances of fetal distress in the UDCA groups compared with placebo (average risk ratio (RR) 0.67; 95% confidence interval (CI) 0.22 to 2.02; five trials, 304 women; random-effects analysis: T² = 0.74; I² = 48%). There were significantly fewer total preterm births with UDCA (RR 0.46; 95% CI 0.28 to 0.73; two trials, 179 women). The difference for spontaneous preterm births was not significant (RR 0.99; 95% CI 0.41 to 2.36, two trials, 109 women).Two trials (48 women) reported lower (better) pruritus scores for S-adenosylmethionine (SAMe) compared with placebo, while two other trials of 34 women reported no significant differences between groups.UDCA was more effective in improving pruritus than either SAMe (four trials; 133 women) or cholestyramine (one trial; 84 women), as was combined UDCA+SAMe when compared with placebo (one trial; 16 women) and SAMe alone (two trials; 68 women). However, combined UDCA+SAMe was no more effective than UDCA alone in regard to pruritus improvement (one trial; 53 women) and two trials (80 women) reported data were insufficient to draw any conclusions from. In one trial comparing UDCA and dexamethasone (83 women), a significant improvement with UDCA was seen only in a subgroup of women with severe obstetric cholestasis (23 women).Danxiaoling significantly improved pruritus in comparison to Yiganling. No significant differences were seen in pruritus improvement with other interventions.Eight trials reported fetal or neonatal deaths, with two deaths reported overall (both in the placebo groups).Women receiving UDCA and cholestyramine experienced nausea, vomiting and diarrhoea. Guar gum caused mild abdominal distress, diarrhoea and flatulence during the first days of treatment. Women found charcoal suspension unpleasant to swallow. Dexamethasone caused nausea, dizziness and stomach pain in one woman.One trial (62 women) looked at the timing of delivery intervention. There were no stillbirths or neonatal deaths in 'early delivery' or the 'await spontaneous labour' group. There were no significant differences in the rates of caesarean section, meconium passage or admission to neonatal intensive care unit between the two groups. AUTHORS' CONCLUSIONS: Different approaches to assessing and reporting pruritus precluded pooling of trials comparing the effects of UDCA versus placebo on pruritus, but examination of individual trials suggests that UDCA significantly improves pruritus, albeit by a small amount. Fewer instances of fetal distress/asphyxial events were seen in the UDCA groups when compared with placebo but the difference was not statistically significant. Large trials of UDCA to determine fetal benefits or risks are needed.A single trial was too small to rule in or out a clinically important effect of early term delivery on caesarean section.There is insufficient evidence to indicate that SAMe, guar gum, activated charcoal, dexamethasone, cholestyramine, Salvia, Yinchenghao decoction (YCHD), Danxioling and Yiganling, or Yiganling alone or in combination are effective in treating women with cholestasis of pregnancy.